2022
DOI: 10.1128/jvi.01015-22
|View full text |Cite
|
Sign up to set email alerts
|

Beta Human Papillomavirus 8 E6 Induces Micronucleus Formation and Promotes Chromothripsis

Abstract: Some beta genus human papillomaviruses (β-HPVs) may promote skin carcinogenesis by inducing mutations in the host genome. Supporting this, the E6 protein from β-HPV8 (8 E6) promotes skin cancer in mice with or without UV exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 87 publications
1
5
0
Order By: Relevance
“…In parallel to clonogenic growth analyses, cytokinesis-block micronucleus assays demonstrated that both E6- and E7-transduced cells already displayed an increase of chromosome breakages compared to control cells at basal (non-irradiated) condition. These interesting observations (exacerbated following irradiation) are in agreement with recent studies analyzing the effect of viral oncoproteins from HPV16 as well as of E6 from cutaneous βHPV8 on genome instability 54 , 55 . Finally, the significant slowing of DNA double-strand break repair kinetics observed in case of viral oncoprotein expression further supported the E6/E7-dependent increase of cellular radiosensitivity.…”
Section: Discussionsupporting
confidence: 91%
“…In parallel to clonogenic growth analyses, cytokinesis-block micronucleus assays demonstrated that both E6- and E7-transduced cells already displayed an increase of chromosome breakages compared to control cells at basal (non-irradiated) condition. These interesting observations (exacerbated following irradiation) are in agreement with recent studies analyzing the effect of viral oncoproteins from HPV16 as well as of E6 from cutaneous βHPV8 on genome instability 54 , 55 . Finally, the significant slowing of DNA double-strand break repair kinetics observed in case of viral oncoprotein expression further supported the E6/E7-dependent increase of cellular radiosensitivity.…”
Section: Discussionsupporting
confidence: 91%
“…However, in HPV-infected cells, p53 is degraded by E6, and Rb is inactivated by E7, both of which result in cell cycle progression to S phase even in the presence of DNA damage, increasing the likelihood of CIN and micronuclei formation [ 64 , 65 , 66 ]. Several serotypes of the β-HPV genus can also induce the formation of micronuclei and subsequently increase tumorigenic mutations in nonmelanoma skin cancer [ 58 ]. HPV8 E6 reduces the availability of Bloom syndrome protein (BLM), which is involved in resolving chromosome bridges during anaphase and facilitating faithful chromosome segregation and results in an increased frequency of micronuclei [ 58 , 67 ].…”
Section: Hpv Induces Specific Types Of Cinmentioning
confidence: 99%
“…Several serotypes of the β-HPV genus can also induce the formation of micronuclei and subsequently increase tumorigenic mutations in nonmelanoma skin cancer [ 58 ]. HPV8 E6 reduces the availability of Bloom syndrome protein (BLM), which is involved in resolving chromosome bridges during anaphase and facilitating faithful chromosome segregation and results in an increased frequency of micronuclei [ 58 , 67 ]. Similarly, HPV38 E6 (also in the β-HPV genus) was shown to be capable of increasing the frequency of micronuclei, although it remains elusive whether the underlying mechanism is identical to that of HPV8 E6 [ 58 ].…”
Section: Hpv Induces Specific Types Of Cinmentioning
confidence: 99%
See 2 more Smart Citations